MEASURES FOR INCREASING PRODUCTION GROWTH AND SWEET CORN ( Zea mays saccharata Sturt) ORGANIC LIQUID FERTILIZER APPLICATION THROUGH COW URINE AND COMPOST BUNCH EMPTY PALM OIL - Irna Syofia; Rahmi Zulhida; Koko Lesmana Bintoro (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
The research objective was to determine growth and yield of sweet corn through the application of organic manure and compost cow urine oil palm empty fruit bunches. This study was conducted in June 2015 to August 2015 in the research field Meteorology and Geophysics Agency (BMKG) subdistrict Percut Sei Tuan, Deli Serdang, with altitude ± 25 m above sea level. This study uses a randomized block design (RAK) factorial with two factors, namely Liquid Organic Fertilizer Urine Cow (S) with 4 levels, namely S0 = 0 ml/tanaman, S1 = 40 ml / plant, S2 = 80 ml / plant and S3 = 120 ml / plant. The second factor is a factor Compost Oil Palm Empty Fruit Bunch (K) with 3 levels, namely K1 = 1.5 kg / plot, K2 = 3 kg / plot and K3 = 4.5 kg / plot. The parameters used in the study that plant height, number of leaves, stem diameter, days to flowering, weight cob with husk per plant, weight of cob without husk per plant, weight of cob without husk per plot, diameter cob without husk, length of cob without husk, and the number of rows per ear. The data were analyzed using ANOVA and continued with different test Mean according to Duncan (DMRT) with a level of 5%. The results showed that administration of liquid organic fertilizer of cow urine with dose 120 ml / plant)gave the highest growth in plant height, number of leaves, stem diameter, days to flowering and production weights cob without husk per plant, weight of cob without husk per plot, length cob without husk, the number of rows per ear, composting empty oil palm bunches dose 4.5 kg / plot gave the highest growth in plant height, number of leaves, stem diameter, days to flowering and production weights cob without husk per plant, weight of cobs without husk per plot, the length of the cob without husk, the number of rows per ear, while the provision of liquid organic fertilizer of cow urine at a dose of 120 ml / plant and compost empty fruit bunches of palm oil at a dose of 3 kg / plot gives the highest production on the weight of cob without husk per plant, giving liquid organic fertilizer cow urine at a dose of 80 ml / compost plants and oil palm empty fruit bunches at a dose of 4.5 kg / plot gives the highest production on the cob without husk weight per plot.Keywords: sweet corn , fertilizer liquid organic cow urine , compost oil palm empty fruit bunches